Un estudio de tecnología lítica desde la antropología de las técnicas : el caso del Alero Deodoro Roca ca. 3000 AP, Ongamira, Ischilín, Córdoba - Caminoa, José María, (South American archaeology series ;, 2016)
As part of a series of research projects on the archaeology of hunter-gatherers societies in the Southern Pampean Hills this presents, among other things, the study of various aspects of the organization of lithic technology and strategies for the use of lithic resources by prehistoric populations. This is in order to understand the social aspects that allow us to recognize and describe habitus or ways of doing things. In this book we studied lithic assemblages, in the manner described above from stratigraphic levels of the Alero Deodoro Roca (Deodoro Roca Rockshelter) comprising chronologies between ca. 3000 years BP to ca. 3600 years BP.